2017
DOI: 10.1016/j.ajog.2017.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pregnancy, birth, and infant outcomes in twins: effects of maternal fertility status and infant gender combinations; the Massachusetts Outcomes Study of Assisted Reproductive Technology

Abstract: Background It is unknown whether the risk of adverse outcomes in twin pregnancies among subfertile women, conceived with and without in vitro fertilization (IVF), differ from those conceived spontaneously. Objective To evaluate the effects of fertility status on adverse perinatal outcomes in twin pregnancies on a population basis. Study Design All twin live births of ≥22 weeks’ gestation and ≥350 grams birthweight to Massachusetts resident women in 2004–10 were linked to hospital discharge records, vital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 87 publications
2
38
1
Order By: Relevance
“…Our prior analyses of twin pregnancies (which were additionally linked to hospital discharge data, as well as birth certificates) have reported a 2-fold increased risk of uterine bleeding and placental complications (abruptio placenta, placenta previa, vasa previa) in subfertile and IVF pregnancies. 34 Nationally in the United States, cesarean rates parallel advancing maternal age: in 2015, women aged 40 years were more than twice as likely to deliver by cesarean as women age <20 years (48.4% vs 20.4%). 1 In 2015, the overall low-risk cesarean delivery rate (cesarean delivery among nulliparous women with full-term singletons in a vertex presentation) was 25.8%, ranging from 16.7% for women ages <20 years to 52.0% for women ages 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior analyses of twin pregnancies (which were additionally linked to hospital discharge data, as well as birth certificates) have reported a 2-fold increased risk of uterine bleeding and placental complications (abruptio placenta, placenta previa, vasa previa) in subfertile and IVF pregnancies. 34 Nationally in the United States, cesarean rates parallel advancing maternal age: in 2015, women aged 40 years were more than twice as likely to deliver by cesarean as women age <20 years (48.4% vs 20.4%). 1 In 2015, the overall low-risk cesarean delivery rate (cesarean delivery among nulliparous women with full-term singletons in a vertex presentation) was 25.8%, ranging from 16.7% for women ages <20 years to 52.0% for women ages 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…The first analysis of perinatal outcomes from the MOSART study was based on singleton and twin births in 2004–08, and examined four adverse outcomes: preterm birth, low birthweight, small for gestational age, and perinatal death (30). In this analysis, based on births in 2004–10, we have increased the sample size by nearly 50% (singleton births from 320,135 to 459,623), expanded the number of adverse outcomes from four to 15 (six maternal and nine infant), and separated the analysis by plurality, with the results in singletons presented in this paper, and the results for twins (further divided by like gender and unlike gender pairs) in a subsequent paper (40). This analysis was repeated and expanded to clarify associations, and to further identify factors that may be in the pathway between fertility status, treatment, and perinatal outcomes.…”
Section: Introductionmentioning
confidence: 93%
“…CART analysis found that at the beginning of pregnancy oocyte donation is the most discriminating factor for severe acute maternal morbidity. This increased maternal risk in women with twin pregnancies after IVF contradicts some previous studies exploring this association [9,[18][19][20]. The latter, however, were limited by their inability to differentiate between spontaneous pregnancy and ovulation-inducing drugs alone and between in vitro fertilization with autologous and donated oocytes.…”
Section: Discussionmentioning
confidence: 73%